Occupational Risks in Midwifery: From Bernardino Ramazzini to Modern Times - Tommaso Bianchi; Michael Belingheri; Antonella Nespoli; Giovanni De Vito; Michele A. Riva (Elsevier, 2019)
Occupational risks are often underestimated in midwifery. It is not commonly known that occupational risks were originally described by the Italian physician Bernardino Ramazzini (1633-1714) at the beginning of the 18th century. Our aim was to describe occupational risks in midwifery from Ramazzini to modern times. The original text by Bernardino Ramazzini was analyzed. A review of modern scientific articles on occupational risks in midwifery was conducted. Ramazzini identified two major occupational risks in midwifery: infections and awkward postures. Modern literature seems to agree with his considerations, focusing on infection, use of universal protection and personal protective equipment, and musculoskeletal problems. Modern studies also evidenced posttraumatic stress disorder that was probably postulated by Ramazzini himself. The poor number of articles in literature on midwives' occupational risks shows a lack of interest toward this issue. Prevention should therefore be emphasized in this field, so high-quality studies on occupational risks in midwifery are needed. Keywords: Bernardino Ramazzini, History, Midwifery, Occupational risks